2009
DOI: 10.1002/job.583
|View full text |Cite
|
Sign up to set email alerts
|

Psychological ownership: theoretical extensions, measurement and relation to work outcomes

Abstract: Viewing psychological ownership as a positive resource for impacting human performance in organizations, the present study investigated the components of an expanded view of psychological ownership. Confirmatory factor analyses on a proposed measure of psychological ownership provided support for a positively-oriented, ''promotion-focused'' aspect of psychological ownership comprised of four dimensions: self-efficacy, accountability, sense of belongingness, and self-identity. In addition, territoriality was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
821
3
23

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 652 publications
(941 citation statements)
references
References 59 publications
32
821
3
23
Order By: Relevance
“…Furthermore, psychological ownership has important emotional, attitudinal, and behavioral effects on employees that experience ownership (Pierce et al 2001). Many scholars are interested in what constitutes employees' ownership and its outcomes (Avey et al, 2009). Van Dyne and Pierce (2004) found that psychological ownership was associated with increased organizational commitment, job satisfaction, organization-based self-esteem, and organizational citizenship.…”
Section: A Psychophysical Ownership As a Determinant Of Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, psychological ownership has important emotional, attitudinal, and behavioral effects on employees that experience ownership (Pierce et al 2001). Many scholars are interested in what constitutes employees' ownership and its outcomes (Avey et al, 2009). Van Dyne and Pierce (2004) found that psychological ownership was associated with increased organizational commitment, job satisfaction, organization-based self-esteem, and organizational citizenship.…”
Section: A Psychophysical Ownership As a Determinant Of Organizationmentioning
confidence: 99%
“…As noted above, Mayhew et al (2007) revealed that organization-based psychological ownership has a positive relationship with affective organizational commitment and job satisfaction. Avey et al (2009) showed that psychological ownership was positively related to transformational leadership, organizational citizenship, affective commitment, job satisfaction, and intention to stay, and negatively related to workplace deviance.…”
Section: A Psychophysical Ownership As a Determinant Of Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The second article, by Avey, Avolio, Crossley, and Luthans (2009) offers the construct, psychological ownership, as a positive resource for impacting performance in organizations. Using a primary sample of 316 employees from a wide range of organizations, the authors provided psychometric scale validation to their measure of psychological ownership.…”
Section: Special Issue Articles: Can Positive Research Build Strongermentioning
confidence: 99%
“…It can help employee to make judgment of responsibility before whether they will initiate dedicate moral actions. In general, developing accountability-based moral ownership entails clarifying what is expected of the individual in his or her role and recognizing that individual for stepping up and taking appropriate responsibility or action (Avey et al ., 2009). It was associated with one's self-identity that they can become viewed as an extension of the self.…”
Section: Theoretical Hypothesismentioning
confidence: 99%